IMPACT OF VIDEOSURGERY TRAINING IN GENERAL SURGERY RESIDENTS WITH LOW FIDELITY SIMULATOR ADAPTED FROM THE FUNDAMENTS OF LAPAROSCOPIC SURGERY (FLS) - Rosa, Luciana Walger Collaço Gomes (2024)
Introduction: Teaching in surgery must follow the evolution of medical techniques, procedures and technology. Since the 90s videosurgery has been developing and nowadays is the gold standard for many procedures in general surgery. As there are different characteristics from conventional surgery, residents need to practice in order to adapt to simulators. The world medical literature has established many training programs among them the Fundaments of laparoscopic Surgery (FLS). Evaluation of surgical technical abilities is a major tool for the residency programs. Objectives: To assess the effect of training acquiring skills of residents at first and second postgraduated level year (PGY1 and PGY2) before and after practice using low fidelity simulator based on tasks from FLS. Methods: A prospective study was conducted to determinate skills acquisition of residents at first and second postgraduated level year l (PGY1 and PGY2) before and after standardized practice using low fidelity simulator. Conclusions: There was a significant improve of the technical abilities reaching levels of improvement. Resident’s performance was evident in the sample groups. First year residents (PGY1) achieved knowledge retention after training similar to the performance of second in the initial assessment, suggesting that the sequenced training carried out is equivalent to one year of practice in the general surgery residency program